Anthropogenic Disturbances Have Contributed to Degradation of River Water Quality in Arid Areas - Li Ji (MDPI AG, 2021)
The earth has been reshaped for millennia. The accelerating pace of anthropogenic activities has generated enormous impacts on the water environment. As one of the main drivers of landscape change, anthropogenic disturbance has brought many negative effects on rivers. Studying the relationship between anthropogenic disturbances and river water quality is of significance for regional conservation and ecosystem management, while the relationship remains poorly understood in the current. In this study, we quantified anthropogenic disturbances by introducing the concept of the hemeroby index and evaluated rivers’ water quality in eight sub-watersheds on the Loess Plateau. The results indicated that 37.5% of the sub-watersheds were in Eutrophic status, and 62.5% were in Marginal water quality index. The river water quality was most poor in the southwestern region near the Yellow River with high-level anthropogenic disturbance. A correlation analysis between water quality indicators and hemeroby suggested that anthropogenic disturbance contributed to a significant water quality deterioration trend (p < 0.01). The river water quality was relatively sensitive to the changes of completely disturbed land-use covers, including urban and industrial land. Our findings provide theoretical guidance for regional water resources conservation and ecosystem management in arid areas.